New records of mites (ACARI: PROSTIGMATA) on Vitis sp. (L.) in Brazil - Andrade-Bertolo, Fernanda de Oliveira; de Moura, Raquel Bottini; Matioli, Andre Luis; Ott, Ana Paula (Comunicata Scientiae, 2013)
Tetranychus mexicanus (McGregor, 1950) (Tetranychidae) was found on leaves of grapevines (Vitis vinifera L. and V. labrusca L.) in Caxias do Sul, RS, Brazil. This is the first register of this mite species occurring on grapevine in South Brazil. Also Phytonemus pallidus (Banks, 1898) and Tarsonemus confusus Ewing, 1939 (Tarsonemidae) were found on grapevine leaves (V. vinifera) in Sant’Ana do Livramento, RS, Brazil. This is the first register of these tarsonemids species occurring on grapevine in Brazil.